Analisa Penerapan Interoperabilitas, Transparansi Informasi, Bantuan Teknis dan Pengambilan Keputusan terhadap Peningkatan Kualitas SDM yang Berorientasi ke Industrialisasi 4.0 Pada UMKM - Nining Suryani; Windi Baskoro P; Hulaifi Hulaifi; Muhammad Sopiyana (Universitas Pamulang, 2023)
This research aims to determine the quality of human resources by using supporting variables such as the role of interoperability, information transparency, technical assistance and decision making. Current developments certainly require higher quality human resources to support better industrial sectors. With the help of supporting technology, sufficient information, technical assistance provided and appropriate decision making, it is hoped that it will be able to become a supporting factor in improving the quality of human resources. This research is a type of research using design. The research method used is a quantitative approach with associative methods. The Associative Method aims to determine the influence or relationship between two or more variables. The type of data used is primary data obtained using questionnaire techniques, interviews, observations and in-depth interviews. The sampling technique is probability sampling. With data analysis SPSS is used for quantitative data, the data analysis steps used in this research are validity and reliability analysis, descriptive analysis, multiple linear regression analysis, classical assumption test, coefficient of determination test and hypothesis testing. The results of the research show that the variables Implementation of Interoperability, Information Transparency, Technical Assistance, and Decision Making together show a positive and significant influence on the HR Quality Improvement variable.